2017
DOI: 10.1136/bmjopen-2016-013460
|View full text |Cite
|
Sign up to set email alerts
|

Cost-effectiveness of superficial femoral artery endovascular interventions in the UK and Germany: a modelling study

Abstract: ObjectivesTo assess the lifetime costs and cost-effectiveness of 5 endovascular interventions to treat superficial femoral arterial disease.DesignA model-based health economic evaluation. An existing decision analytical model was used, with updated effectiveness data taken from the literature, and updated costs based on purchasing prices.SettingUK and German healthcare perspectives were considered.ParticipantsPatients with intermittent claudication of the femoropopliteal arteries eligible for endovascular trea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 20 publications
0
7
0
Order By: Relevance
“…We read the full text of the remaining ten articles and excluded one article because of its design and a further three because they were not economic evaluations. Our literature search resulted in six studies that fulfilled inclusion criteria (1823).
Figure 1.PRISMA flowchart for study selection.
…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…We read the full text of the remaining ten articles and excluded one article because of its design and a further three because they were not economic evaluations. Our literature search resulted in six studies that fulfilled inclusion criteria (1823).
Figure 1.PRISMA flowchart for study selection.
…”
Section: Resultsmentioning
confidence: 99%
“…Most studies (83.3 percent) did not state the aspects of the system in which the decision needed to be made or for which the economic evaluation had been designed (1822). In addition, very few studies (33.3 percent) reported the choice of discount rate used for costs and outcomes and explained why it was appropriate (18;23). We noticed that the authors correctly stated the time horizon over which costs and consequences had been evaluated, but they rarely explained why the time period chosen was appropriate (33.3 percent) (2023).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although stent placement is associated with higher initial costs, this might be compensated for if the additional placement of a stent results in better clinical outcomes and correspondingly lower hospital costs. 10,11 Several randomised clinical trials suggest that in short stenoses or occlusions, the PTA-S has no benefit over PTA alone. 12e14 The use of a stent in patients with longer lesions has been shown to have beneficial effects on clinical success and freedom from revascularisation.…”
Section: Introductionmentioning
confidence: 99%
“…12e14 The use of a stent in patients with longer lesions has been shown to have beneficial effects on clinical success and freedom from revascularisation. 11,13 A recent systematic review found a short-term benefit for the stented group at 6 months, but this was lost at 12 month follow up. 15 However, it is important that these results be interpreted with caution, as many of these studies are sponsored by stent supplying companies which might have led to bias.…”
Section: Introductionmentioning
confidence: 99%